SURGICAL AND ORTHODONTIC TREATMENT OF TEMPOROMANDIBULAR JOINT ANKYLOSIS - Giacomo Gobbo Trojan; Pamela Rufina Stefanello Wideck; Isabella Rayane de Souza Torres; Lívia Numeriano de Sá Gomes Vilarim; Victoria Carminatti Silveira; Rene Rodrigues Vieira; Maria Eduarda Cardoso Malheiros de Sena; Rebeca Pires de Castro; Laís Gomes do Nascimento (International Journal of Health Management Review, 2026)
Temporomandibular joint (TMJ) ankylosis is characterized by the bony, fibrous, or fibro-osseous fusion of articular surfaces, resulting in severe limitation of mouth opening and compromising masticatory and phonatory functions, as well as oral hygiene. When it manifests during childhood or persists for extended periods, it can lead to craniofacial developmental disorders, such as facial asymmetry, micrognathia, retrognathism, and malocclusions. This study aimed to analyze the main surgical and orthodontic approaches used to treat dentofacial deformities associated with TMJ ankylosis. To this end, a narrative literature review was conducted using the PubMed database, with the search terms "Temporomandibular Joint Ankylosis" and "Orthodontics" combined by the Boolean operator AND. Articles published within the last five years, available in Portuguese or English and directly related to the topic, were selected. The results demonstrated that treatment must be individualized and multidisciplinary, involving oral and maxillofacial surgery, orthodontics, and, if necessary, prosthetic rehabilitation. Key surgical approaches include gap arthroplasty, interpositional arthroplasty, costochondral grafting, and distraction osteogenesis. Orthodontic intervention proved fundamental for correcting occlusal discrepancies and establishing a functional and aesthetic occlusion. It is concluded that combining surgical and orthodontic treatments, alongside postoperative physical therapy, is essential for restoring mandibular function and reducing the risk of recurrence.